Modeling of Active Heave Compensation System for Seafloor Drill - Jin, Yongping; Liu, Guangping; Li, Lanxiang; Peng, Youduo; Wan, Buyan (Journal of Vibration Testing and System Dynamics, 2026)
Aiming at the influences of wave in the process of launch & recovery of the seafloor drill, a velocity sensor is used to gather the data of the heave motion of ship, and a mathematical model of active heave compensation hydraulic serve control system for seafloor drill is established. The simulation of this model based on PID control is performed. The results show that the heave motion compensation control of seafloor drill using PID control makes the tracking accuracy more than 90%. This will improves the reliability and security of the seafloor drill in the process of launch and recovery.